Implementation of Maqashid Syariah in the Development of the Halal Industry in Indonesia - Andi Firmansyah; Mochamad Yulian Frizky (Universitas Negeri Surabaya, 2025)
This article discusses the implementation of maqashid sharia in the halal industry in Indonesia. With the welfare of the people as the main goal, maqashid sharia creates a framework that supports sustainability and ethics in the halal industry. This study explores the principles of maqashid sharia which include protection of life, mind, descendants, property and religion, and their implications for halal industry policies and practices. Through the analysis that has been carried out, it is hoped that it can be used in developing an optimal strategy for sustainable halal industry growth, and in accordance with sharia values, which will provide wider social and economic benefits for Indonesian society. The method used is a literature review method through various sources of literature spread across the Internet. The results obtained that one of the biggest challenges in implementing maqashid sharia in the development of the halal industry is that there are several production actors who still often ignore social benefits, and prioritize individual or personal interests. So there needs to be optimization and emphasis on responsibility by producers so that they can participate in improving community welfare.